Microscopic events in β-hairpin folding from alternative unfolded ensembles - Best, Robert B. (National Academy of Sciences, 2011)
We have performed the first unbiased folding simulations of the GB1 hairpin in explicit solvent, using hundreds of microsecond-long molecular dynamics simulations (total time: 0.7 ms). Our simulations are initiated from two sets of structures. Starting from an equilibrium unfolded state, we obtain single-exponential folding kinetics with rate coefficients in good agreement (T = 350 K) or within an order of magnitude (T = 300 K) of the experimental values. However, simulations initiated from unfolded configurations lacking secondary structure result in biexponential kinetics with an additional fast nanosecond kinetic mode. This mode can strongly bias the folding rate estimated from the mean first passage time, when the trials are much shorter than the folding time. We find that the mechanism of the hairpin folding is insensitive to the details of the initial unfolded ensemble and is initiated by correct formation of the turn of the hairpin, followed by the formation of the native hydrogen bonds and hydrophobic contacts, consistent with experimental ϕ-value analysis. Subsequent native interactions can be formed either from the turn or from the hairpin termini, helping to explain an apparent discrepancy in experimental results. From our simulations, we also obtain the transition path durations, a critical parameter for single molecule experiments aiming to resolve events along folding pathways. The lengths of transition paths span a wide range, from 50 ps to 140 ns, at 300 K.